Digital Contact Tracing in the EU: Data Subject Rights and Conflicting Privacy Governance - Rosenberger, Alex; Shvartzshnaider, Yan; Sanfilippo, Madelyn (Proceedings of the Association for Information Science and Technology, 2021)
The wide‐spread use of digital exposure notification systems, often called contact tracing apps, raises questions about privacy and efficacy of technosolutionism to address COVID‐19. As part of a broad study of global contact tracing apps, this poster explores the governance and privacy implications of European digital contact tracing solutions. We explore legal justifications for data collection in these apps and data subjects' rights with respect to the General Data Protection Regulation (GDPR) and national laws throughout Europe.